Navigating Digital Payments: Understanding Student Adoption of the DANA App Through User Experience, Security, and Social Influence - Chandini, Anggella; Lusiana, Finola Fiftem Eka Puti, Jefri Andriadi, Mardifa Wahyu Putri, (YUME : Journal of Management, 2025)
The rapid advancement of financial technology has transformed consumer payment behaviors, particularly among university students who frequently engage with digital payment applications. This study explores the key factors influencing the adoption and continued use of the DANA mobile payment application among students at UPI YPTK Padang using a qualitative research approach. Semi-structured interviews were conducted with purposively selected participants to gain in-depth insights into their experiences. Thematic analysis revealed four primary factors shaping adoption: perceived ease of use, security concerns, promotional incentives, and social influence. Convenience and an intuitive user interface were identified as critical enablers of sustained usage, aligning with the Technology Acceptance Model. However, concerns regarding data privacy and fraud remained significant barriers, emphasizing the need for enhanced security measures. Promotional incentives, such as cashback offers and discounts, played a crucial role in motivating users, while peer recommendations were found to be a key determinant of adoption. These findings provide valuable implications for fintech companies seeking to enhance user engagement, suggesting a need for a balanced approach that integrates usability, security, financial incentives, and social influence. Future research should consider comparative studies across different demographic groups and longitudinal analyses of mobile payment behaviors. Keywords: Mobile payment adoption, fintech, DANA application, university students, digital payment behavior